Role of the central region of NifL in conformational switches that regulate nitrogen fixation. (20th January 2006) - Little, R.; Martinez-Argudo, I.; Dixon, R.
Abstract : The NifL regulatory protein is an anti-activator that tightly regulates transcription of genes required for nitrogen fixation in Azotobacter vinelandii by controlling the activity of its partner protein NifA through the formation of a protein–protein complex. NifL modulates the activity of NifA in response to the redox, carbon and nitrogen status to ensure that nitrogen fixation occurs only under physiological conditions that are appropriate for nitrogenase activity. The domain architecture of NifL is similar to that of some histidine protein kinases, with two N-terminal PAS (P ER, A RNT, S IM) domains, one of which contains an FAD cofactor that senses the redox status, and a C-terminal domain containing conserved residues that constitutes the nucleotide-binding domain of the GHKL (g yrase, H sp90, histidine k inase, MutL ) superfamily of ATPases. We have evidence that the central region of NifL, which is located between the PAS domains and the C-terminal GHKL nucleotide-binding domain, plays a crucial role in the propagation of signals perceived in response to the redox and fixed nitrogen status and that this region participates in conformational changes that switch NifL between active and inactive states. We have identified a critical arginine residue in the central region of NifL that participates in the conformational switch that activates NifL. Mutations in the central region of NifL that disable the redox-sensing function of NifL but leave the protein competent to respond to the nitrogen signal conveyed by the signal transduction protein GlnK have also been isolated. Our results suggest that the topological relationship between the central region and the GHKL domain may alter as a consequence of conformational changes induced in response to signal perception.